Linaria pseudamethystea (Antirrhineae, Plantaginaceae), a new species mimetic of and apparently sympatric with L. amethystea - Blanca, Gabriel; Carmona, Rafael; Cueto, Miguel; Fuentes, Julián (Phytotaxa, 2023)
Linaria pseudamethystea, from the south-western part of the Iberian Peninsula, is here newly described, illustrated, and compared with its morphologically closest relatives from L. sect. Supinae: L. amethystea, L. semialata, and L. diffusa. The species is characterized by being annual and glabrous and by having a loose inflorescence; calyx lobes unequal; corolla blue-violet, with conspicuous dark veins and yellow to orangish palate, abaxial lip with two prominent humps and ornamentation reticulate and often with two thick spots, and spur equalling the length of the rest of the corolla, curved, usually dark blue-violet; capsule globose and glabrous; seeds black with densely papillose and non-tuberculate disk, and non- thickened wing. L. pseudamethystea is an endemic species, whose general morphology and distribution area overlap with that of L. amethystea, causing confusion between the two species and misidentification of their populations. The new species grows in ephemeral therophyte pastures of siliceous mountains, from the east of the province of Seville (Spain) to the Algarve and Alentejo (Portugal).